TIDAL PATTERNS AND RESOURCE USE IN THE MUSI-BANYUASIN COASTAL ZONE OF SUMATRA - Hadi, Safwan; Hanson, Arthur J.; Koesoebiono, -; Mahlan, Musrefinah; Purba, Mulia; Rahardjo, Santoso (Marine Research in Indonesia, 1977)
Tidal influence extends 100 km upriver in the coastal swamplands of Sumatra and Kalimantan. In planning development or resource use, description of local tidal variation is important since tides interact with river flow to zone the land and waters into a series of distinctive environments. The coastal swamps are being opened for rice cultivation with tidally-influenced irrigation and drainage canals. There are also forestry and fishery activities plus major shipping activities in these delta areas. The tidal patterns arc studied in the South Sumatra coastal portion of the Musi and Banyuasin River basins. The tides are mixed, predominantly diurnal with a maximum range of 3.5 m near the coast. Significant differences in tidal amplitude and phase exist between rivers separated by deltas often less than 10 km in width. Differences in river water flow atributed to season or basin characteristics influence tidal patterns. On the Musi river the relationship between tidally-influenced resource uses and distance from the sea suggests the greatest variety of activities occurs within the zone of maximum tidal range 0 to 30 km from the delta fronts. This zone should therefore be considered a region of special ecological concern. A mechanism is needed for coordinated planning of infrastructure changes likely to influence hydrology or resource uses. Predictive models should be developed for measuring the likely impact of such development on coastal hydrology.